Desain klaster rantai pasok rumput laut di Kabupaten Bombana - Annaastasia, Nurhuda; Mansyur, Akhmad; Fiar Erawan, Muhammad Trial; Siang, Roslindah Daeng; Mangurana, Wa Ode Intiyani (Universitas Halu Oleo, 2024)
The effort to realize a local development plan in achieve development vision one of the is make strong intervention in seaweed farming sector. This research is aims to develop a ready to process seaweed business development cluster, formulate institutional patterns of seaweed marketing in the center area of ​​seaweed Small and Medium Industries in Bombana Regency and integrating seaweed downstream into business incubation system in Bombana Regency. This research was conducted from July to November 2022 in Bombana Regency. The research show that Areas that are eligible to become seaweed business development zones in Bombana Regency are located in three clusters, namely Rumbia, Poleang and Kabaena. Of the three clusters, the Rumbia cluster is in the first hierarchy in the composition of the preparation of seaweed business development. Types of seaweed that have the potential to be developed in the Rumbia and Poleang clusters are: Eucheuma spinosum, Eucheuma cottoni and Gracilaria, while in the Kabaena cluster it is Eucheuma spinosum, Eucheuma cottoni. Processed seaweed products that can be recommended for production are:Alkali Treated Cottoni (ATC), Semi Refined Carrageenan (SRC) and Refined Carrageenan (RC) to support the development of the existing seaweed industry for the improvement of the regional economy. Sequentially the seaweed supply beach starts from the seaweed farmer (production margin 9,55%), seaweed farmer group (market margin 0,28%) cooperative society/BUMDES (market margin 11,61%), Agroindustry (PT. INRI with market margin 50,67% and buyer export. Seaweed agroindustry is a puller company that absorbs all seaweed production produced by seaweed farmer.